Promotion of private investment and public-private partnerships in the Arequipa región, at means to reduce infrastructure gaps and economic growth. - Brunno Alonso Gambetta Paredes (2019)
The objective of this article is to make known the implications related to the infrastructure gap that our economy has been going through, the same which has affected various productive sectors and the economic growth of the Arequipa región and the country as a whole. Likewise,the article seeks to demonstrate how this can be alleviated through the promotion of private investment and the development of Public Private Partnerships (PPPs), which must be carried out both at the national government level, through Proinversion and the Ministry of Economy and Finance, and the same, through regional and local governments, through their offices for the promotion of private investment (OPIPs in Spanish). All of the above is framed in the "Law for the Promotion of Private Investment", which came into force in 2008, through Legislative Decree No. 1012, which has been acquiring special importance, due to the current situation that our economy experiences, characterized by subnational governments that in recent years have been receiving less public resources for investment in public infrastructure projects, limiting their capacity to address the problems described above. Finally, some specific actions that the Regional Department for the Promotion of Private Investment of the Regional Government of Arequipa has been carrying out in this area, from its creation to the present, are detailed.